Pengaruh Sosial Terhadap Keputusan Pembelian Produk Mie Instan Indomie (Studi Kasus di Kelurahan Telanaipura Kecamatan Telanaipura Jambi) - Denny Asmas; Ahmad Tarmizi (Universitas Batanghari Jambi, 2020)
The increasing number of residents, especially in Telanaipura Village Telanaipura sub-district will have far-reaching implications also on the decision to purchase instant noodle products. the background outlined above, can be taken to formulate a problem: How social variables affect the decision to buy Instant Indomie noodle products. The purpose of this study is as follows: To analyze the influence of social variables on the decision to buy instant indomie noodle products. To find out the social influence and purchasing decisions used the regression formula. The accumulated results of respondents' answers showed that on average, all respondents' answers showed that the purchase decision variable was at a pretty good level with an average score of 320. The accumulated respondent's response to social variables was 325.8. This value is in a fairly good interval class. This means that social factors are considered by consumers to consume instant indomie noodle food. determination coefficient or (R Square) of independent variable regression (Social Variable) to the Decision to Purchase indomie instant noodle products 0.643. social variable t-calculated value of 2,003, because the t-count value (2,003) is greater than t-Table (1,684) then at the error rate 5% Ho rejected Ha accepted